Nanoencapsulation Techniques in Food Industry - İsmail Tontul (Turkish Journal of Agriculture: Food Science and Technology)
Encapsulation is a technology applied to cover an active material with various materials. In the food industry, encapsulation techniques are applied to protect sensitive components against environmental factors, increase bioavailability of nutrients, controlled release and mask flavor and odor. Nanocapsules are obtained when the size of the obtained encapsulated materials is less than 1 μm. There are many methods for the production of nanocapsules, which are classified as lipid formulation-based nanoencapsulation technologies, natural nanocarrier-based nanoencapsulation technologies, specialized equipment based nanoencapsulation technologies, biopolymer nanoparticle-based nanoparticle technologies and other nanoencapsulation technologies. In this review, information on these technologies used in the nanoencapsulation of food components in accordance with this classification is presented.